Urinary tract infection among people living with human immunodeficiency virus attending selected hospitals in Addis Ababa and Adama, central Ethiopia - Gebremedhin, Ketema Bizuwork; Yisma, Engida; Alemayehu, Haile; Medhin, Girmay; Belay, Girma; Bopegamage, Shubhada; Amogne, Wondwosson; Eguale, Tadesse (Frontiers in Public Health, 2024)
Urinary tract infections (UTIs) and antibacterial resistance (ABR) are the most important public health problems, but not well studied among people living with human immunodeficiency virus (PLHIV) globally, especially in low income countries. Therefore, it is important to regularly measure the extent of the UTIs and ABR in the most susceptible populations. This study aimed to investigate prevalence of UTIs, associated factors, bacterial causal agents and their antibiotic susceptibility profile among PLHIV in central Ethiopia.A hospital-based cross-sectional study was conducted to recruit 688 PLHIV by simple random sampling method. Background information were gathered through interviews while clinical information were gathered from recent information sheets of patient charts using organized, pretested, and validated study tool. Midstream urine was collected aseptically and transported to Microbiology Laboratory of Aklilu Lemma Institute of Pathobiology within four hours of collection maintaining its cold chain. Standard conventional microbial culture methods and matrix-assisted laser desorption ionization-time of flight mass spectrometry were used to identify the bacterial isolates at the species level. Kirby Bauer's disc diffusion method was used to determine the antibiotic susceptibility profile of the bacterial isolates based on the interpretation guideline of Clinical Laboratory Standard Institute. Logistic regression was used to examine factors associated with the occurrence of UTIs with statistical significance level declared at P < 0.05.Out of 688 PLHIV involved in the current study, (n= 144; 20.9%) were positive for UTIs, where the majority were asymptomatic for UTIs. In the multivariable logistic regression analysis, only HIV RNA ≥ 200 copies/ml [AOR = 12.24 (95% CI: 3.24, 46.20), P<0.01], and being symptomatic for UTIs during the study period [AOR = 11.57 (95% CI: 5.83, 22.97), P<0.01] were significantly associated with the occurrence of UTIs.The dominant bacterial species isolated were E. coli (n= 65; 43%) followed by E. faecalis (n= 16; 10.6%), and K. pneumoniae (n= 11; 7.3%).